Applied Internships in Egyptian Tourism Education: Measuring Experiential Learning's Impact on Student Self-Efficacy and Perceived Effectiveness of Academic Materials - Abdelghani, Abdelrahman Ahmed Abdelhai; Ahmed, Hebatallah Ahmed Mokhtar (Journal of Social and Scientific Education, 2025)
This study investigates how applied internships in Egyptian tourism education influence student self-efficacy and perceptions of academic material effectiveness through experiential learning. Grounded in Kolb's Experiential Learning Theory and Bandura's Social Cognitive Theory, the research employs a quantitative cross-sectional survey of 320 final-year tourism students who completed compulsory internships. Results from structural equation modeling reveal that experiential learning intensity significantly enhances student self-efficacy (β = 0.976, p < 0.001) and perceived effectiveness of academic materials (β = 0.247, p < 0.001). Industry-academia alignment fully mediates the relationship between experiential learning intensity and material effectiveness (indirect effect = 0.676, 95% CI [0.584, 0.768]), while skill-transfer perception partially mediates the link to self-efficacy (indirect effect = 0.194, 95% CI [0.094, 0.294]). Internship quality moderates these relationships, strengthening outcomes when high (β = 0.087, p = 0.003). Significant gender disparities emerge, with female students reporting higher self-efficacy and material effectiveness (p < 0.001). The study underscores the need for strategically designed internships, curriculum-industry alignment, and gender-responsive pedagogies to bridge theory-practice gaps in tourism education.